The Family Innovator's Dilemma: How Family Influence Affects the Adoption of Discontinuous Technologies by Incumbent Firms - König, Andreas; Kammerlander, Nadine; Enders, Albrecht (Academy of Management Review, 2013)
We integrate research on family business and discontinuous change to better explain why incumbents vary in when and how they adopt discontinuous technologies. Family influence induces companies to strive for continuity, command, community, and connections and, thus, alters the mix of constraints under which firms operate. Consequently, family influence weakens several of the inertial forces described in the discontinuous change literature, particularly the level of formalization, dependence on external capital providers, and political resistance. However, it also aggravates critical sources of organizational paralysis, specifically emotional ties to existing assets and the rigidity of mental models. We aggregate these seemingly contradictory effects to show that, overall, discontinuous change conflicts with essential goals and values of the family system, and, therefore, family influence entails fundamentally different dilemmas than those described in extant research. In turn, although highly family-influenced companies recognize discontinuous technologies later than their less family-influenced counterparts, they implement adoption decisions more quickly and with more stamina. Moreover, family influence reduces adoption aggressiveness and flexibility. We discuss important implications of our research for conversations on discontinuous change as well as for the debate on the advantages and disadvantages of family influence in firms.